Water-renewable energy Nexus: Optimization of geothermal energy-powered seawater desalination systems. (August 2022) - Pietrasanta, Ariana M.; Mussati, Sergio F.; Aguirre, Pio A.; Morosuk, Tatiana; Mussati, Miguel C.
Abstract: This paper addresses the optimization of geothermal energy-powered seawater desalination systems. A nonlinear optimization mathematical model was implemented into General Algebraic Modelling System (GAMS). The model embeds many candidate configurations for optimization, which result from the combination of the following subsystems: a single flash (SFGP) or double flash (DFGP) geothermal power plants, a multi-effect distillation (MED) process or a reverse osmosis (RO) system for freshwater production. Also, an energy recovery turbine (ERT) is embedded. The minimization of the total annual cost of the process represents the objective function. The proposed model is a powerful decision-making tool for selecting the optimal configuration of the integrated process, sizes, and operating conditions to meet the demands of electricity and freshwater desired by users. It was found that for fixed 70 MW electricity generation and low freshwater demands (720–2880 m 3 /h), the optimal configuration is SFGP/MED. For high freshwater demands (4320–5040 m 3 /h), the optimal configuration is DFGP/MED/RO. For intermediate freshwater demand (3600 m 3 /h), an optimal transition configuration is in between the two previous configurations, i.e., SFGP/MED/RO/ERT. It is highlighted that the model can be used to simulate fixed configurations if no degrees of freedom are available.